Older Workers and Work Exit Preferences in a Digitalized Working Life - Solem, Per Erik; Hauge, Linda; Hellevik, Tale; Herlofson, Katharina (Nordic Journal of Working Life Studies, 2023)
With working life being in the middle of both a demographic and a digital transition, a key question is whether digitalization may counteract the policy goal of delaying work exit. Here, we use survey data from the Norwegian Senior Policy Barometer to investigate the association between how digital tools are experienced and the preference for timing of work exit. We find that, even after controlling for various potential confounders, experiencing digital difficulties at the workplace is correlated with preferring to leave work early. A relevant follow-up question is then which factors increase the likelihood among older workers of experiencing such difficulties. The analyses show that workplace conditions are more important than individual characteristics, suggesting that efforts taken to reduce experiences of digital difficulties at the workplace could be effective in preventing early exits.